Citra Diri Perempuan Indoneia DalamAnalisis Semiotik Sajak-Sajak Nikah Ilalang Karya Dorothea Rosa Herliany The Women Image in Dorothea Rosa Herliany's Nikah Baking: A Semiotic Analysis - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABTSTRACr This study describes the image of woman in Nikah Ilalang (NI) verses according to semiotic way. The manifestation of the image is taken from five verses in NI which are assumed to have the image of woman.The five verses are "Nikah Pisau", "Nikah Ilalang", "Nikah Sungai" "Nikah Perkampungan", and "Pengantin yang Terbaring". All of the verses are dealing with "Marriage", in wich a woman is one of the subject who is taking a part in marital process. This is a qualitative study which applies a semiotic reading method in which the woman image is observed in two-stage-reading. The first is a heuristic reading and secondly, a hermeneutic reading. In this two-stage-reading, the woman image in NI indicates differences. In the heuristic stage of reading, the woman image can only be projected physically or psychologically as a mature persona with a dual personality. The persona has the ferninin characterstics but appears to be masculine. The woman is psychologically disappointed upon her suffering which is out of her conscious keep pressing her in her involvement within the patriarchal world. The disappointment is compensated in the form of rude speeches in addition to her out of house-world exploration. The woman in NI is a coward creature who hides behind her rude speeches. Keywords: woman image â semiotics - heruristic - hermeneutic. .